Scientific Grey Literature in a Digital Age: Tracking its Use and Influence in an Evolving Information Economy - Hutton, Gregory R. G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper outlines methodologies to improve understanding of the influence of grey literature published in print and digital formats. The study is based on analyses of citation data regarding the UN-based Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection collected from Web of Science, Google, and Google Scholar. Cet article propose des méthodologies pour améliorer notre compréhension de l'influence de la littérature grise publiée sous forme imprimée ou numérique. L'étude est fondée sur des analyses de données de citation concernant le groupe d'experts conjoint de l'ONU chargé d'étudier les aspects scientifiques de la protection du milieu marin recueillies dans Web of Science, Google et Google Scholar.